A surface micromachined broadband millimeter-wave filter using quarter-mode substrate integrated waveguide loaded with complementary split ring resonator (2014)
A millimeter-wave bandpass filter (BPF) using complementary split-ring resonator (CSRR) loaded quarter-mode substrate integrated waveguide (QMSIW) cavities is presented in this work. The CSRR-loaded QMSIW cavity resonates below the original QMSIW resonance frequency, which further reduces the size with respect to its SIW counterpart. The reduced quality factor Q of the cavity makes it useful for BPFs with broad fractional bandwidth (FBW). A micromachined 4th order Chebyshev BPF is demonstrated at the unlicensed 57 GHz to 64 GHz frequency band. A FBW of more than 11.6% with an in-band return loss of better than 15 dB, and an insertion loss of less than 2.5 dB are obtained. © 2014 IEEE.